The tuning of light-matter coupling and dichroism in graphene for enhanced absorption: Implications for graphene-based optical absorption devices. (11th February 2016) - Rakheja, Shaloo; Sengupta, Parijat
Abstract: The inter-band optical absorption in graphene characterized by its fine-structure constant has a universal value of 2.3% independent of the material parameters. However, for several graphene-based photonic applications, enhanced optical absorption is highly desired. In this work, we quantify the tunability of optical absorption in graphene via the Fermi level, angle of incidence of the incident polarized light, and the dielectric constants of the surrounding dielectric media in which graphene is embedded. The influence of impurities adsorbed on the surface of graphene on the Lorentzian broadening of the spectral function of the density of states is analytically evaluated within the equilibrium Green's function formalism. In all the cases, we find that absorption of light graphene embedded in dielectric medium is significantly higher than 2.3%. We also compute the differential absorption of right and left circularly-polarized light in graphene that is uniaxially and optically strained. The preferential absorption or circular dichroism is investigated for armchair and zigzag strain and the interplay of k -space and velocity anisotropy is examined. Finally, we relate circular dichroism to the Berry curvature of gapped graphene and explain the connection to parameters that define the underlying Hamiltonian.